Biological activity of phenolic compounds from argentinean herbs infusions - Rodriguez Vaquero, Maria Jose (2014)
Argentinean herbal infusions were studied for their beneficial biological properties and secondary metabolites content, such as phenolic compounds in order to find new natural products beneficial. The modifications of antihypertensive and antioxidant activities by the addition of commonly used additives (lemon, sugar and sweetener) were studied also. Ilex paraguaiensis infusion showed the highest concentration of phenolic compounds and flavonoid fraction, the supplementation with lemon juice increased the phenolic compound content. All infusion showed high DPPH radical scavenging assays and additives did not modify significantly this activity. The infusion of I. paraguaiensis presents the maximum viability reduction of Escherichia coli and Staphylococcus aureus and the herbs combination Lippia integrifolia-Ilex paraguaiensis was the most effective to reduce S. aureus and E.coli viability. The phenolic compounds concentration as well as the qualitative composition of each infusion plays an important role in the antimicrobial activity. Because the high correlation between the concentration of total phenolic compounds and antioxidant and antihypertensive activities, we can infer that the phenolic compounds are responsible for such activities. The results obtained allow us to propose the herbs studied as potential natural antioxidants and antihypertensive compounds that could be used in pharmaceutical and food industries.